(3efJgi GdJUQjM HNdGUI Gdbhd GdUQjM aj Yde GdJTQjMs - (3GdOefghQj , CMeO Hf YHO GdefYe Hf jhSa Hf UjGe GdOefghQj, SQGL GdOjf,J (B1192 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3ajbhd GdeJYKQ HCPjGd GdNLd gPG eGdNUJg ef cJGHi Gdbhd GdUQjM djSgd JfGhdg Ydi GdeTJZdjf HYde GdJTQjM hdHYO YPG Gdaf Yf CPgGf GdWGdHjf s
(3BNQgG (B:s
(3dG jUM JTNjU eQV hYdGLg EdG HYO eYQaI Yde GdJTQjM hai gPG GdbOQ caGjI def jQjO GdTQhY ai Yde GdJTQjM ef Cgd GdYfGjI s
(3QJHg GdeDdas
(3cCUdg Ydis
(3ebOeI hHGHjf hNGJeIs
(3gfGc Tc CfgG HNW GdeDda s
(3GdeDda cGf TjNkG ddCRgQ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs